Recent developments in modelling preferences: Uncertainty and ambiguitiy - Colin F. Camerer; Martin Weber (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1991)
In subjective expected utility (SEU) the decision weights people attach to events are their beliefs about the likelihood of events. Much empirical evidence, inspired by Ellsberg (1961) and others, shows that people prefer to bet on events they know more about, even when their beliefs are held constant. (They are averse to "ambiguity", or uncertainty about probability.) We review evidence, recent theoretical explanations, and applications of research on ambiguity and SEU.
Keywords: D81; C91; 650; Ambiguity; uncertainty; Ellsberg paradox; non-expected utility